Notes on the poikilochlorophyllous desiccation-tolerant plants - Tuba, Zoltán (Acta Biologica Szegediensis, 2008)
The desiccation-tolerant (DT) plants are poikilohydric and capable of surviving the loss of 90-95% of their cell water content. DT plants are important constituents of many ecosystems from the arctic (lichen and moss vegetations) to the tropics (lichen, moss and flower vegetations). Desiccation-tolerant (DT) plants may be subdivided into homoiochlorophyllous (HDT) and poikilochlorophyllous (PDT) types. The HDTs retain their chlorophyll on desiccation, whereas in PDTs desiccation results in the loss of chlorophyll, which must be resynthetized following remoistening. The PDT strategy can be seen an the evolutionarily different new strategy. It is based on the dismantling of internal chloroplast structure by an ordered deconstruction process during drying, and its resynthesis upon rehydration. The selective advantage of poikilochlorophylly is in minimising photo-oxidative damage and not having to maintain an intact photosynthetic system through long (5-10 months) inactive periods of desiccation. Taxonomically the PDT plants appear to be restricted to the monocots. The HDT and PDT strategies solve the same ecological problem, but cover a broad temporal range of adaptation.